2004
DOI: 10.1063/1.1834996
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic trapping of small particles by sharp edges vibrating in a flexural mode

Abstract: Ultrasonic trapping of small particles by sharp edges vibrating in a flexural mode is reported. Two rectangular metal plates with a sharp edge are mechanically excited to vibrate in a flexural mode by the piezoelectric rings which are pressed between them by a bolt structure. Small particles such as mint seeds and flying color seeds can be attracted to the sharp edges of the plates. Relationship between input power applied to the piezoelectric rings and the number of trapped particles is experimentally investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…Employing lab-fabricated, focusing ultrasonic transducers from Y-cut LN in thickness-mode operation at 23-37 MHz, they were able to trap and retain oleic acid drops of around 125 m diameter in water in a region of a few hundred microns in size. Hu et al (2004) presented a simple arrangement to trap individual particles, brine shrimp, thyme, salt crystals, and similar objects with a size of around 50-900 m, in the pressure node between vibrating, tapered beams while operating in air or water. This route came about from the group's work in acoustic levitation, and indeed the literature in that area, for example, Hertz (1995), is worth consulting in considering new ideas for trapping particles with acoustics.…”
Section: In Closed Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Employing lab-fabricated, focusing ultrasonic transducers from Y-cut LN in thickness-mode operation at 23-37 MHz, they were able to trap and retain oleic acid drops of around 125 m diameter in water in a region of a few hundred microns in size. Hu et al (2004) presented a simple arrangement to trap individual particles, brine shrimp, thyme, salt crystals, and similar objects with a size of around 50-900 m, in the pressure node between vibrating, tapered beams while operating in air or water. This route came about from the group's work in acoustic levitation, and indeed the literature in that area, for example, Hertz (1995), is worth consulting in considering new ideas for trapping particles with acoustics.…”
Section: In Closed Environmentsmentioning
confidence: 99%
“…Circumventing the limitations of current microfluidics technology is indeed critical to delivering on its idyllic promises (Ho et al, 2011), from handheld medical diagnostic devices for the rapid detection of single molecules associated with heart disease (Gerszten and Wang, 2008), cancer (Lu et al, 2005), and physiological fluid chemistry (Craighead, 2006), to water purification (Shannon et al, 2008) and polymerase chain reaction on a chip (Huang et al, 2006). Fortunately, acoustic wave technology at the microscale to nanoscale is helping to make these things reality, as will be shown, and furthermore promises to allow researchers to produce and exploit interesting physical phenomena seen at the microscale-to-nanometer scale.…”
mentioning
confidence: 99%
“…The length of the metal wire bundle immersed in water was about 3 mm. When a driving voltage with a frequency close to the resonance frequency was applied to the ultrasonic transducer, the thickness mode vibration could be excited in the transducer [13][14][15]. This resulted in an ultrasonic vibration in the thin metal wires.…”
Section: Construction and Principlementioning
confidence: 99%
“…Ten copper wires with a diameter of 199 m each form the bundle, and the bundle length is 38 mm beyond the stainless steel plates. The ultrasonic transducer has a sandwich structure with a multi-layer piezoelectric vibrator at the center, which is formed by four piezoelectric rings (C203, Fuji Ceramics, Japan) [13][14][15]. The outer diameter, inner diameter and thickness of each piezoelectric ring are 20, 12 and 2.4 mm, respectively.…”
Section: Construction and Principlementioning
confidence: 99%
“…In literature, particle attraction to oscillating structures has previously been observed in centimeter-scaled setups: The attraction of ∼ 1 mm particles to oscillating sharp edges (Hu et al 2004), rods (Liu and Hu 2009), and needles (Hu et al 2007) was reported in the kHz range. In these cases, the described physical effects were also based on acoustic radiation forces, yet with a different structural setup and physical modeling.…”
mentioning
confidence: 95%